The C. elegans Observatory: High-throughput exploration of behavioral aging - Kerr, Rex A.; Roux, Antoine E.; Goudeau, Jérôme; Kenyon, Cynthia (Frontiers in Aging, 2022)
Organisms undergo a variety of characteristic changes as they age, suggesting substantial commonality in the mechanistic basis of aging. Experiments in model organisms have revealed a variety of cellular systems that impact lifespan, but technical challenges have prevented a comprehensive evaluation of how these components impact the trajectory of aging, and many components likely remain undiscovered. To facilitate the deeper exploration of aging trajectories at sufficient scale to enable primary screening, we have created the C. elegans Observatory, an automated system for monitoring the behavior of group-housed C. elegans throughout their lifespans. One Observatory consists of a set of computers running custom software to control an incubator containing custom imaging and motion-control hardware. In its standard configuration, the Observatory cycles through trays of standard 6 cm plates, running four assays per day on up to 576 plates per incubator. High-speed image processing captures a range of behavioral metrics including movement speed and stimulus-induced turning, and a data processing pipeline continuously computes summary statistics. The Observatory software includes a web interface that allows the user to input metadata and to view graphs of the trajectory of behavioral aging as the experiment unfolds. Compared to manual use of a plate-based C. elegans tracker, the Observatory reduces effort required by close to two orders of magnitude. Within the Observatory,reducing function of known lifespan genes with RNA interference (RNAi) gives the expected phenotypic changes, including extended motility in daf-2(RNAi) and progeria in hsf-1(RNAi). Lifespans scored manually from worms raised in conventional conditions match those scored from images captured by the Observatory. We have used the Observatory for a small candidate-gene screen and identified an extended youthful vigor phenotype for tank-1(RNAi) and a progeric phenotype for cdc-42(RNAi). By utilizing the Observatory, it is now feasible to conduct whole-genome screens for an aging-trajectory phenotype, thus greatly increasing our ability to discover and analyze new components of the aging program.